2013
DOI: 10.1016/j.ccr.2013.06.014
|View full text |Cite|
|
Sign up to set email alerts
|

Hexokinase 2 Is Required for Tumor Initiation and Maintenance and Its Systemic Deletion Is Therapeutic in Mouse Models of Cancer

Abstract: Summary Accelerated glucose metabolism is a common feature of cancer cells. Hexokinases catalyze the first committed step of glucose metabolism. Hexokinase 2 (HK2) is expressed at high level in cancer cells, but only in a limited number of normal adult tissues. Using Hk2 conditional knockout mice, we showed that HK2 is required for tumor initiation and maintenance in mouse models of KRas-driven lung cancer, and ErbB2-driven breast cancer, despite continued HK1 expression. Similarly HK2 ablation inhibits the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
667
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 733 publications
(699 citation statements)
references
References 34 publications
29
667
3
Order By: Relevance
“…Instead, the expression of hexokinase 2 (HK2) was significantly up-regulated in HCC with a single lesion, but was kept unchanged in the HCC with multiple lesions. Recent studies have demonstrated that the HK2 could promote glycolysis in tumor cells but not in normal cells [60,61], and increase the tumor progression and aggressive behaviors in many cancers [62][63][64][65]. Palmieri et al have reported that the poor patient survival and the metastasis of breast cancer to the brain were significantly associated with high HK2 expression [66], and HK2 ablation even could inhibit the metastasis [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the expression of hexokinase 2 (HK2) was significantly up-regulated in HCC with a single lesion, but was kept unchanged in the HCC with multiple lesions. Recent studies have demonstrated that the HK2 could promote glycolysis in tumor cells but not in normal cells [60,61], and increase the tumor progression and aggressive behaviors in many cancers [62][63][64][65]. Palmieri et al have reported that the poor patient survival and the metastasis of breast cancer to the brain were significantly associated with high HK2 expression [66], and HK2 ablation even could inhibit the metastasis [61].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the HK2 could promote glycolysis in tumor cells but not in normal cells [60,61], and increase the tumor progression and aggressive behaviors in many cancers [62][63][64][65]. Palmieri et al have reported that the poor patient survival and the metastasis of breast cancer to the brain were significantly associated with high HK2 expression [66], and HK2 ablation even could inhibit the metastasis [61]. Therefore, the up-regulation of HK2 might associate with the larger tumor size and early tumor recurrence/metastasis features of the HCC with a single lesion as previously reported [19,67].…”
Section: Discussionmentioning
confidence: 99%
“…This physical association facilitates glucose phosphorylation and protects cell from apoptosis (Pastorino & Hoek 2003). HK2 is highly expressed in lung and breast cancer and is required by proliferating cancer cells as demonstrated by the impairment of tumour progression following its downregulation (Fang et al 2012, Patra et al 2013. In the unbound state, HK2 exists in an open inactive structure (Fig.…”
Section: Effect Of Metformin On Glucose Metabolism In Cancermentioning
confidence: 99%
“…An increase in glucose uptake and a shift toward aerobic glycolysis are commonly observed in several tumors. In breast cancers, mammary tumor-initiating cells (TICs) and undifferentiated basal-like mammary tumors (i.e., those mostly enriched in TICs) require glycolysis for self-renewal [36][37][38]. Strikingly, aerobic glycolysis is sufficient, at least in vitro, to induce malignant phenotypes in breast cancer cells [39].…”
mentioning
confidence: 99%